Anticoagulated de novo atrial flutter complicated by transitory ischemic attack in fatal COVID‐19. Issue 1 (20th January 2022) - Finsterer, Josef; Wilfing, Astrid
Abstract: SARS‐CoV‐2 may not only manifest as pneumonia (COVID‐19) but also in other organs, including the brain (neuro‐COVID). One of the cerebral complications of SARS‐CoV‐2 is ischemic stroke. Transitory ischemic attack (TIA) in a SARS‐CoV‐2 positive has not been reported. A 78‐year‐old poly‐morbid male (diabetes, hypertension, and coronary heart disease), admitted for COVID‐19, developed atrial flutter on hospital day (hd) 2. Anticoagulation with enoxaparin was started. On hd5, he experienced a TIA despite sufficient anticoagulation. The patient expired on hd28 due to multi‐organ failure from sepsis due to superinfection with staphylococcus aureus. Infection with SARS‐CoV‐2 may be complicated by atrial flutter. Atrial flutter may be complicated by TIA despite sufficient anticoagulation, suggesting that standard anticoagulation may be insufficient to meet SARS‐CoV‐2‐associated hypercoagulability syndrome. Forced anticoagulation and adequate antibiosis in poly‐morbid SARS‐CoV‐2‐infected patients with hypercoagulability and cytokine storm are warranted. Abstract : SARS‐Cov‐2 infection may be complicated by atrial flutter, hypercoagulability, TIA, superinfection, and sepsis.